The evaluation of potato virus Y transfer by some beneficial bugs (Hemiptera: Heteroptera) - IRINA M PAZYUK; TATYANA S FOMINYKH (Society for Indonesian Biodiversity, 2019)
Abstract. Pazyuk IM, Fominykh TS. 2019. The evaluation of potato virus Y transfer by some beneficial bugs (Hemiptera: Heteroptera). Biodiversitas 20: 1222-1227.  The predatory bugs Podisus maculiventris, Orius majusculus, Nesidiocoris tenuis, and Macrolophus pygmaeus were commonly used for control of pests in potato meristem culture in greenhouses. In this study, the risk of transmission of potato virus Y (PVY) by entomophagous bugs was estimated in cage experiments. It has been shown that none of the bugs tested was capable of transmitting the PVY. However, N. tenuis and M. pygmaeus have been shown to damage potato seedlings in the absence of animal food (pests or factitious food). The bug N. tenuis caused severer damage to potato plants than did the bug M. pygmaeus. Therefore, we can recommend only P. maculiventris and O. majusculus for pest control in potato meristem culture in greenhouses.